PARTIAL CHRONIC TOXICITY TEST OF COPPER (Cu2+), ZINC (Zn2+) and CYANIDE (Cn+) FOR YOUNG COBIA FISH (Rachycentron canadum) - Dung, Le Quang; Cu, Nguyen Duc (Marine Research in Indonesia, 2008)
The partial toxicity tests of copper (Cu2+), zinc (Zn2+) and cyanide (CN-) for young cobia (Rachycentron canadum) fishes 45 days-old were conducted in Doson station during ten days (yr 2005). These three toxic substances affected strongly the growth rate of the Cobia fish (length and weight of the body), even at the lowest treated concentration. The LC50 values of copper, zinc and cyanide were 0.32 mg l-1; over mg l-1 and 0,049 mg l-1, respectively. Based on the statistical analysis of growth rate of cobia by determining 1C25, IC50, NOEC and LOEC values, we have addressed the safe concentrations of these two heavy metals and cyanide in the environmental aquaculture which must be lower than 0.025 mg Cu l-1, 0.5 mg Zn l-1 and 0.005 mg CN l-1, respectively. The result also showed that cyanide was the most toxic to Cobia, followed by copper and zinc.